Are returns to mothers' human capital realized in the next generation? The impact of mothers' intellectual human capital and long-run nutritional status on children's human capital in Guatemala - Behrman, Jere R.; Murphy, Alexis; Quisumbing, Agnes R.; Yount, Kathryn M. (International Food Policy Research Institute, 2009)
Many prior studies find significant cross-sectional positive ordinary least squares (OLS) associations between maternal human capital (usually maternal schooling attainment) and children's human capital (usually children's schooling, but in some cases children's nutritional status). This paper uses rich Guatemalan longitudinal data collected over 35 years to explore several limitations of these standard" estimates. The preferred estimates developed herein suggest that (1) maternal human capital is more important than suggested by the standard estimates; (2) maternal cognitive skills have a greater impact than maternal schooling attainment on children's biological human capital; and (3) for some important indicators of children's human capital, maternal biological capital has larger effect sizes than maternal intellectual capital (schooling and cognitive skills). These results imply that breaking the intergenerational transmission of poverty, malnutrition, and intellectual deprivation through investments in women's human capital may be more effective than previously suggested, but it will require approaches that account for dimensions of women's human capital beyond just their schooling. Effective interventions to improve women's biological and intellectual human capital often begin in utero or in early childhood; thus, their realization will take longer than if more schooling were the only relevant channel."